Step-by-step explanation:
6b x>=1
6c y>7
7a x>3
7b -2<=2x<6
-1<=x<3
answer:-1,0,1,2,3
D) EFGH moved onto E'F'G'H after rotating 180 counterclockwise around the origin and the reflecting across the y-axis.
<h3>How to carry out transformations?</h3>
From online resources gotten about this question, for quadrilateral EFGH and quadrilateral E'F'G'H to be congruent, what we must do first is to rotate 180° counterclockwise around the origin and then move EFGH onto E'F'G'H'.
The last step to get this proof of congruency is to reflect across the y-axis.
Read more about transformations at; brainly.com/question/4289712
#SPJ1
Answer:
The larger of the two is 44.67
Step-by-step explanation:
let the first number=x
let the second number=y
We can derive a system of equations using the mathematical statements
Their sum is 33:
x+y=33( call this equation 1)
Sum of first number and four times the second is -2:
x+4y=-2(call this equation 2)
Since the integer coefficients of x in both equations are the same we can quickly subtract one from the other to eliminate it
For this explanation, I choose to subtract equation 1 from 2
(x+4y=-2)-(x+y=33)=3y=-35
y=-35/3
Now plug in the value of y into any equation for that of x. Say we plug into equation 1
x+(-35/3)=33
x-35/3=33( multiply through by 3)
3x-35=99
3x=99+35
3x=134
x=134/3
Therefore,x=134/3 or 44.67 and y=-35/3 or -11.67
1. correct- factor: 4
2. correct- factor: 4
3. Incorrect- The polynomial is not prime, and the factored polynomial is 4(2x-3)
4. Incorrect